2010
DOI: 10.1007/s00264-010-0998-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of iloprost treatment for osseous malperfusion

Abstract: Insufficient osseous blood supply results in bone marrow oedema (BMO) and/or avascular necrosis (AVN). One treatment option to support osseous perfusion is the application of stable prostacycline analog iloprost. In this clinical study, 95 patients were treated with iloprost for BMO/AVN. One hundred eighty-six bones were affected by BMO/AVN before treatment. Average follow-up was 33.0± 17.6 months. Pain levels could be reduced (e.g. visual analogue scale, 5.0±2.2 points reduced to 1.7±2.2 points) and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 25 publications
1
44
0
9
Order By: Relevance
“…The drug is given as intravenous infusions over 5 days at doses between 25 and 50 mg per day. It has been shown to be efficacious in the treatment of BML at various locations, 64 avascular osteonecrosis, except for terminal cases, 63 and regional transient osteoporosis. 65,66 One study compared the effects of iloprost and the bisphosphonate ibandronate on BMLs in the knee and found similar results with around 47% reduction in BMLs and improvement of pain and functions scores.…”
Section: Pharmaceutical Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug is given as intravenous infusions over 5 days at doses between 25 and 50 mg per day. It has been shown to be efficacious in the treatment of BML at various locations, 64 avascular osteonecrosis, except for terminal cases, 63 and regional transient osteoporosis. 65,66 One study compared the effects of iloprost and the bisphosphonate ibandronate on BMLs in the knee and found similar results with around 47% reduction in BMLs and improvement of pain and functions scores.…”
Section: Pharmaceutical Optionsmentioning
confidence: 99%
“…It is thought that prostaglandin I2 (or prostacyclin) and its analogues promote bone regeneration on a cellular or a systemic level and improve microcirculation in the area. 62,63 One prostacyclin derivative, iloprost, has demonstrated beneficial effects on BML. The drug is given as intravenous infusions over 5 days at doses between 25 and 50 mg per day.…”
Section: Pharmaceutical Optionsmentioning
confidence: 99%
“…However, long-term effective dose of these drugs may bring severe adverse reaction of livers and muscles [10]. Enoxaparin, which is of Anticoagulants, and Iloprost, which is of Vasodilators, can relieve the pain of early-staged primary ONFH patients with tendency of thrombosis and with low fibrinolytic activity, but cannot reverse the necrotic process [11] [12]. Alendronate, as an osteoclast inhibitor, can improve clinical symptoms; retard joint collapsing and replacement time.…”
Section: Discussionmentioning
confidence: 99%
“…Medical therapies as well as nonpharmacological therapies, including modified weight bearing, hyperbaric oxygen and extracorporeal shock wave therapy, have been the subject of multiple investigations, including several prospective studies. 18,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] Bisphosphonates have received specific attention owing to their known effect of decreasing osteoclast-mediated bone turnover that theoretically could prevent subchondral bone collapse. A randomized controlled trial assessing 54 hips reported significantly lower rates of disease progression and need for arthroplasty in patients treated with bisphosphonates for 2 months.…”
Section: Discussionmentioning
confidence: 99%